Outcomes after Cognitive Perceptual Motor Retraining (CPM) of Patients with Acquired Brain Injury (ABI) - Kara Christy; Natasha Huffine; Tammy Hannah; Marita B. de Leon (Scholarworks @ WMU, 2016)
Background: Remediation of deficits is one approach used by occupational therapists in the treatment of clients with acquired brain injury (ABI). This retrospective study examined outcomes after participation in Cognitive Perceptual Motor Retraining (CPM) of clients with ABI and identified demographic and injury characteristics of clients that were associated with outcomes. CPM was delivered as part of the standard treatment and was not designed for research purposes. Method: A retrospective review of 59 client records was completed. CPM evaluation test scores, demographic information, and injury characteristics were extracted from the records. Results: There were moderate improvements in CPM test scores and good discharge outcomes for most clients. Discharge to home with independent status was associated with mild to moderate traumatic brain injury severity and being married. Longer time since injury and having a concurrent psychiatric diagnosis were associated with longer duration of CPM. Conclusion: This preliminary study demonstrates positive therapy outcomes after CPM. Recommendations were made for future research and considerations in the use of CPM. These include the need for addressing concurrent needs, such as psychological issues and repeated re-evaluations, to determine when clients have met maximum remediation and thereby minimizing cost.